A Large-Class Undergraduate Microbiology Laboratory Activity on Microbial Diversity and Antimicrobial Resistance - Farkas, Kata (J Microbiol Biol Educ, 2020)
The investigation of microbial diversity and adaptation is essential to comprehend biological processes. Yet, teaching basic microbiology techniques to large groups of students in limited time is challenging, as most approaches are time-consuming or require special equipment. In this activity, students performed three laboratory exercises in three hours involving the analysis of inoculated agar plates they prepared by swabbing samples from an environment of their choice, the examination of antimicrobial effects on growth, and the assessment of microbial enzymatic activity in soil. The activity was field tested in two classes (70 and 76 students, respectively) of first-year undergraduate biology and zoology students at the Bangor University (UK) using pre- and post-tests (n = 84). Based on the answers, learning gain scores (G) were calculated for each learning objective (LO). For all LOs, the mean post-test scores were higher than the mean pre-test scores. The activity significantly improved students’ understanding of microbial diversity (G = 0.36, p = 0.010) and microbial detection and quantification (G = 0.18 to 0.773, p ≤ 0.004). The lack of significant differences in scores for questions targeting microbial growth (G = 0.31, p = 0.292) and antimicrobial resistance (G = 0.38, p = 0.052) suggested some existing knowledge amongst undergraduates. However, the extent of knowledge showed great variation. The results may suggest that the activity is suitable to introduce microbiology-related laboratory work to students with limited laboratory skills and knowledge. Furthermore, the pre- and post-test approach used here is suitable for both course evaluation and monitoring attainment and can be used for program validation and quality control.